PENGARUH BEST AVAILABLE RATE (BAR) DAN NILAI TUKAR MATA UANG TERHADAP REVENUE PER AVAILABLE ROOM (REVPAR) DI THE ALENA RESORT - I Gusti Agung Gede Witarsana; Ni Made Suastini; Wayan Aniek Juniarista (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The development of business in the accommodation service sector in Bali createscompetition to obtain income that matches or even exceeds the target, so hotelsneed to improve performance. Revenue Per Available Room (RevPAR) is one ofthe keys to measuring hotel performance. To maximize revenue without reducingguest satisfaction, The Alena applies a price policy of Best Available Rate (BAR).This BAR is applied using nominal US dollars (USD) so that the exchange rate(USD against rupiah) will affect RevPAR which must be reported using thenominal rupiah. This study aims to determine the effect of the Best Available Rateand Currency Exchange Rate on Revenue Per Available Room at The Alena Resortin 2017 to 2019. The results show that BAR (X1) and currency exchange rates (X2)have a significant effect on RevPAR ( Y) at The Alena Resort, both partially andsimultaneously which contributed 31.4% while the remaining 68.6% wasinfluenced by other variables not examined in this study.